PENINGKATAN KETERAMPILAN MENGHIAS HANTARAN PERNIKAHAN MELALUI MEDIA VIDEO TUTORIAL PADA PEMBELAJARAN KETERAMPILAN VOKASIONAL SUVENIR BAGI SISWA DISABILITAS INTELEKTUAL RINGAN - Ulfahniyanti, Sri; Rahmahtrisilvia , Rahmahtrisilvia; Nurhastuti , Nurhastuti; Nasri, Yosa Yulia (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study aimed to improve wedding gift decoration skills through the use of video tutorial media in vocational souvenir learning for a student with mild intellectual disability in Grade XI at SLB Mutiara Qalbu Sungai Limau. The research employed Classroom Action Research (CAR), which focuses on the systematic and reflective improvement of instructional practices through two action cycles. Each cycle consisted of the stages of planning, action implementation, observation, and reflection, with video tutorials utilized as visual support in vocational skills instruction. The research subject was a student with mild intellectual disability, identified by the initials RS, who experienced difficulties in practice-based vocational skills. Data were collected through performance observation and practical tests of wedding gift decoration and analyzed descriptively to describe changes in the learning process and outcomes. The findings indicate that the use of video tutorial media contributed to improvements in the learning process, increased student engagement and focus, and supported greater independence in completing the sequential steps of wedding gift decoration tasks. Through a systematic, gradual, and continuous action process, the student’s vocational skills developed and reached the expected learning mastery criteria.